LITERATURE REVIEW: IMPLEMENTATION OF BUSINESS PROCESS MANAGEMENT IN BUSINESS MODEL MANAGEMENT TO IMPROVE THE QUALITY AND EFFICIENCY OF HEALTH SERVICES - Susyanti, Jeni; Noor, Meitria Syahadatina; Shaddiq, Syahrial (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This literature review analyzes the crucial role of Business Process Management (BPM) as a vital instrument in Business Model Management (BMM), especially in the context of health care facilities. By synthesizing findings from various scientific studies, this article highlights how BPM facilitates the optimization of clinical and administrative workflows, which in turn improves service quality, operational efficiency, and patient satisfaction. The review identifies trends, challenges, and success factors in integrating BPM into the healthcare business model framework, and underscores the potential of BPM to drive innovation and adaptation of business models amid an ever-evolving healthcare landscape